Equality without equity: The gender pay gap at the National University of Colombia - Eduardo Rodríguez; Carolina Neira; Álvaro Valdés (Latin American Economic Review, 2021)
The National University of Colombia boasts a clear and egalitarian salary regime for its academic staff. Apart from rules concerning maternity and paternity leaves, which follow national Colombian legislation, the Academic Personal Statute is completely free of gender-based norms. Salaries are assigned through a points system that considers training level, productivity, and academic rank. With this in mind, one might expect to find egalitarian male and female salary conditions free of the gender-related gaps existing in other, more arbitrary private work environments. In this article, we present the results of a variance decomposition analysis of the gross salaries of all full-time professors and report the existence of an unadjusted gender pay gap of 0.12 and adjusted or unexplained gaps of 0.07-0.09 obtained through a Mincer earnings regression and a Blinder-Oaxaca decomposition. Partial correlations between these gaps and the different factors that come into play are examined and analyzed. The high impact of professors' research track record on their salaries appears as the main contribution to the gender differences. It seems plausible that the crucial need for time to dedicate to research opens the window to the patriarchal society to permeate the otherwise egalitarian salary regime of the University, especially for the highest range of salaries corresponding mainly to male full professors who are very active in research.
Keywords: I23; C2; C55; J16; J31; 330; Gender Pay Gap; Blinder-Oaxaca Decomposition; Mincer Earnings Regression; Gender Equity; Data Analysis; Wage Structure; Wage Differentials; Higher Education